DI JALUR PENERBANGAN AIRASIA DALAM PENGENDALIAN RASA TAKUT ZAINAL MUTTAQIN SEORANG PEKERJA SEJATI - FL. Sudiran (DEDIKASI : Jurnal Ilmiah Sosial, Hukum, Budaya, 2015)
This research is very simple one because it is the experience of a man who is accustomed to fly .He is Mr.Zainal Mutaqin the high manager in Jawa Post group.The researcher will know the feeling during his travel by AirAsia aircraft where everybody feels afraid of after the flight accident in West Kalimantan on 28  ,December 2014.The method of the research is by library research and the main news is taken from The DailyNewspaper KaltimPost in Samarinda ,East Kalimantan .It takes 2 months research by reading and clipping the daily newspaper concerned.The result of the research is that firstly if someone has much experience in flying he or she does not feel  afraid of and groggy as well.For him or her there is no fear of flying.Secondly , he is a real officer . The suggestion is that hi experience must be socialize to the passengers in flight continually.